Determinants of Capital Structure in the Stock Exchange of Thailand: A Comparative Analysis between Industrial Products and AGRO Industries - Sroythong, Suwichada; Nantapate, Pornwan (Sripatum Review of Humanities and Social Sciences, 2026)
This study aims to investigate factors influencing capital structure of companies listed on the Stock Exchange of Thailand. The samples are classified into two groups. The first group is the industrial products industry, which is more sensitive to economic uncertainty, comprising 89 companies. The second group is the AGRO industry, which is less sensitive to economic uncertainty, comprising 48 firms. Quarterly panel data are collected from the first quarter of 2021 to the fourth quarter of 2025 with a total of 20 periods. Descriptive statistics are employed for this analysis while inferential statistics are conducted using Multiple Regression Analysis. The findings reveal that growth opportunity, asset tangibility, non-debt tax shield, and firm size have statistically significant positive relationships with capital structure in both industries. In contrast, liquidity ratio and return on assets exhibit statistically significant negative relationships with capital structure across both industries. However, firm age shows a statistically significant negative relationship with capital structure only in the industrial products industry. In addition, revenue volatility demonstrates a statistically significant positive relationship with capital structure only in the AGRO industry. The results indicate that industry type plays an important role in determining corporate capital structure.